DEVIATION BY THE EMPLOYER FROM ITS OWN DISCIPLINARY CODE WHEN CONDUCTING DISCIPLINARY INQUIRIES - R Jordaan-Parkin (Obiter, 2022)
Is it expected of the employer to strictly adhere to the terms and conditions of its own disciplinary code when conducting disciplinary proceedings against an employee? The purpose of this note is to address this question and investigate the approach of the courts towards such a deviation by the employer from its own disciplinary code. It seems to be clear that no uniformity exists in the approach of the courts towards this issue.